Prognostic Significance and Functional Relevance of Olfactomedin 4 in Early-Stage Hepatocellular Carcinoma. Issue 1 (January 2020) - Ye, Liangtao; Kriegl, Lydia; Reiter, Florian P.; Munker, Stefan M.; Itzel, Timo; Teufel, Andreas; Ziesch, Andreas; Török, Helga Paula; Kirchner, Thomas; Gerbes, Alexander L.; Guba, Markus; Mayerle, Julia; et al.
Abstract : OBJECTIVES: Hepatocellular carcinoma (HCC) is a leading cancer-related cause of death. Unfortunately, recurrence is common even after curative treatment of early-stage patients, and no adjuvant treatment has yet been established. Aberrant expression of OLFM4 in human cancers has been reported; yet, its specific function during tumor development remains poorly understood, and its role in HCC is unknown. The purpose of this study is to examine the prognostic significance of OLFM4 and its functional relevance in determining recurrence in patients with early-stage HCC. METHODS: Immunohistochemical staining to assess expression, cellular distribution, and prognostic significance of OLFM4 was performed in a tissue microarray comprising 157 HCC tissues and matched nontumor tissues. In addition, expression of OLFM4-coding mRNA was assessed in a separate patients' cohort. The findings were validated by in vitro functional studies using siRNA directed against OLFM4 to assess its effect on cell motility and proliferation. RESULTS: The fraction of HCC samples exhibiting positive OLFM4 staining was higher in comparison with that observed in hepatocytes from matched nontumor tissue (61% vs 39%). However, cytoplasmic-only staining for OLFM4 was associated with vascular invasion ( P = 0.048), MMP-7 expression ( P = 0.002), and poorer survival ( P = 0.008). A multivariate analysis confirmed the independent significance of OLFM4 in determining patients' outcome (5-year survival [58.3% vs 17.3%; HR: 2.135 95% confidence interval: 1.135–4.015; P = 0.019]). Correspondingly, inhibition of OLFM4 by siRNA modulated the expression of MMP-7 and E-cadherin, causing inhibition of cell proliferation, motility, and migration. DISCUSSION: To the best of our knowledge, we provide the first report on the prognostic significance of OLFM4 in HCC and identify its mechanistic role as crucial mediator of MMP family protein and E-Cadherin in determining cell invasion and metastasis formation.